2015
DOI: 10.1186/s12937-015-0069-1
|View full text |Cite
|
Sign up to set email alerts
|

Fast food increases postprandial cardiac workload in type 2 diabetes independent of pre-exercise: A pilot study

Abstract: BackgroundType 2 diabetes aggravates the postprandial metabolic effects of food, which increase cardiovascular risk. We investigated the acute effects of fast food on postprandial left ventricular (LV) function and the potential effects of pre-exercise in type 2 diabetes individuals.MethodsWe used a cross-over study including 10 type 2 diabetes individuals (7 male and 3 females; 53.4 ± 8.1 years; 28.3 ± 3.8 kg/m2; type 2 diabetes duration 3.1 ± 1.8 years) and 10 controls (7 male and 3 females; 52.8 ± 10.1 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…Still, our findings suggest that HIIT was a more potent stimulus for improving global cardiac function and myocardial contractility than MICT. This is consistent with evidence from adults with chronic disease 18,19,[30][31][32] and animal models [33][34][35] . Wisloff et al (2007) showed that twelve weeks of HIIT was superior to MICT and standard care for improving EF (10pp or 35% increase, P<0.020) in patients with stable post infarction heart failure 18 .…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…Still, our findings suggest that HIIT was a more potent stimulus for improving global cardiac function and myocardial contractility than MICT. This is consistent with evidence from adults with chronic disease 18,19,[30][31][32] and animal models [33][34][35] . Wisloff et al (2007) showed that twelve weeks of HIIT was superior to MICT and standard care for improving EF (10pp or 35% increase, P<0.020) in patients with stable post infarction heart failure 18 .…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…This is a sub-study of a randomised, controlled trial [18]. Ten participants with T2D and ten healthy matched controls completed the study.…”
Section: Methodsmentioning
confidence: 99%
“…Blood glucose, C-peptide, plasma triglycerides, total cholesterol, high density lipoprotein and low-density lipoprotein, high-sensitive C-reactive protein and HbA1c were analysed as previously reported in Hollekim-Strand, Malmo [18]. Insulin sensitivity was calculated using the HOMA2 calculator (The Homeostasis Assessment Model, University of Oxford, UK).…”
Section: Methodsmentioning
confidence: 99%
“…122 In addition, recent data indicate that fast food consumption induces greater and sustained overall cardiac workload (prolonged elevations in resting heart rate and prolonged elevations in diastolic workload) in patients with type 2 diabetes. 123 In contrast, the Mediterranean diet which is low in caloric density but rich in nutrient density has been associated with better cardiovascular health. 1 Consumption of fiber is beneficial for postprandial dysmetabolism amelioration.…”
Section: Dietary Modification and Exercisementioning
confidence: 99%